Komunitas Plane Spotter – Kajian Netnografi Terhadap Komunitas Cyber di Media Sosial Instagram @indonesianspotters untuk Meningkatkan Eksistensi Komunitas - Ira Purwitasari; A. Judhie Setiawan (Connected: Jurnal Ilmu Komunikasi, 2021)
This research is motivated by the impact of internet technology in various fields of human life, including cyber community activity. Seeing the phenomenon of the emergence of uniqueness cyber community with a variety of virtual activities the authors are interested in conducting research on Indonesian Plane Spotters Cyber Community and seeing how their activity that they implement on social media Instagram @indonesianspotters. This research uses qualitative approaches and netnography method. The present ethnographic study is being confronted with a cyber community that is conducting its activities in the virtual world. This research highlighted the importance of community members to take part in producing aviation photo in line with the messages they have sent on the instragram @indonesianspotters. The instagram messages were medium as part of efforts to strengthen their existence as Indonesian Plane Spotters.